The The Objectives of Moral Education According to Ibn al-Haytham in the Book Tahdhīb al-Akhlāq: Biography of Ibn al-Haytham - Amin, Habibi; Tamam, Abbas Mansur; Ibadalsyah, Ibadalsyah (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Ibn al-Haytham is widely recognized as a scientist renowned for his expertise in optics. He was also a philosopher in the field of ethics. This unique combination makes his thought particularly compelling to explore, especially in relation to the objectives of moral education. The aim of this study is to examine the goals of moral education from the perspective of a figure who embodies both scientific and philosophical insight. The research employs a qualitative method by analyzing the texts found in Ibn al-Haytham’s work, which serves as the primary object of study. The interpretation is conducted through an educational-philosophical lens, focusing on his moral thought. According to Ibn al-Haytham, the purpose of moral education is to cultivate individuals who are capable of self-reflection, asceticism, intellectual engagement, generosity, love for others, wise use of wealth, and the abandonment of carnal desires, immoral behavior, anger, and self-serving actions.